Krüppel-like transcription factors and control of pluripotency - Bourillot, Pierre-Yves (BioMed Central, 2010)
Recent papers have demonstrated a role for Krüppel-like transcription factors 2, 4 and 5 in the control of mouse embryonic stem cell pluripotency. However, it is not clear whether each factor has a unique role or whether they are functionally redundant. A paper by Parisi and colleagues in BMC Biology now sheds light on the mechanism by which Klf5 regulates pluripotency. See research article http://www.biomedcentral.com/1741-7007/8/128